ORGANIZATIONAL STRUCTURE OF ENTERPRISE - Toshpo’latov Dilshodbek Toshtemir o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The organizational structure of the enterprise is the main mechanism of management and allows you to achieve effectively the goal. Analysis and changes in the organizational structure are necessary in modern market conditions for the successful functioning of any enterprise, while the organizational structure reflects the management scheme of the enterprise, as well as the staffing of the enterprise. The correct distribution of functions between departments and employees of the enterprise is the basis for achieving the goals. The term "organizational structure" refers to the way an organization organizes its workforce so that its tasks and objectives can be accomplished. Formal structure may not be necessary in a small work group where face-to-face communication is common, but in a larger organization, decisions about the delegation of various tasks must be made. As a result, procedures are established to delegate duties to various functions. The organizational structure is established by these choices. What employees do, whom they report to, and, for managers, who they report to, typically define responsibilities in any organization, regardless of size or complexity. These definitions are eventually assigned to positions within the organization rather than to particular people. The work that an organization does is just one of many factors that determine the best organizational structure; its size in terms of the number of employees, revenue, and locations of its facilities and the variety of its businesses (the extent to which it is market-diversified).